(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
We have investigated patho-morphologic findings in some parenchymal and immune organs of sheep infected with high virulent strain ‘’Stavropoliskii’’ of parapoxvirus by a common method (MNS 5451:2005). By means of the microscope were found desquamation of some epithelium of epidermis, eosinophil and lymphocyte infiltration and vacuolization in the derma, and also edema and hyperemia in lung alveoli. Germinal center of lymph nodes was reduced and the number of plasma cells was decreased. Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 66-70